COMPARATIVE ANALYSIS OF TWO METHODS OF SOCKET PRESERVATION PILOT STUDY - Trajculeski, Stavre; Veleska Stevkovska, Daniela; Terzievska, Aneta; Menceva, Zaklina (Medicinski časopis, 2024)
AbstractIntroduction: Volumetric changes of the residual alveolar ridge begin after tooth extraction. They are more pronounced in the vestibule-oral aspect than in the coronary apical aspect. In order to preserve the volume of hard and soft tissues, several types of bone grafts, bone substitutes and biomaterials have been used. PRF as an autologous blood derivative has been used in recent years as an solo graft material or in combination with other graft material.Objective: Clinical and radiological evaluation of two different methods of socket preservation.Material and method: Two study groups of 10 subjects each, with socket preservation with solo PRF and PRF+xenograft. Dimensional changes after 4 and 6 months, density of newly formed bone after 4 months with CBCT 3D imaging technique, postoperative morbidity during the first 7 days after intervention were evaluated.Results: Statistical analysis confirmed lower bone resorption in the PRF+GRAFT test group compared to the PRF group. Better density of newly formed bone in the PRF+GRAFT group and better ratio between the density in the socket and the density in the periapical region. Decreased postoperative morbidity in both groups.Conclusion: Recommendation for the use of PRF as an adjuvant with other grafts and substitutes, and as a solo graft material.
Keywords: Keywords: A-PRF, xenograft, CBCT, socket preservation, guided bone regeneration.